Opposite changes in cannabinoid CB1 and CB2 receptor expression in human gliomas - De Jesús, Maider López; Hostalot, Cristina; Garibi, Jesús M.; Sallés, Joan; Meana, J. Javier; Callado, Luis F. (Neurochemistry international, 2010)
Gliomas are the most important group of malignant primary brain tumors and one of the most aggressive forms of cancer. During the last years, several studies have demonstrated that cannabinoids induce apoptosis of glioma cells and inhibit angiogenesis of gliomas in vivo. As the effects of cannabinoids rely on CB(1) and CB(2) receptors activation, the aim of the present study was to investigate both receptors protein expression in cellular membrane homogenates of human glial tumors using specific antibodies raised against these proteins. Additionally, we studied the functionality of the cannabinoid receptors in glioblastomas by using WIN 55,212-2 stimulated [(35)S]GTPgammaS binding. Western blot analysis showed that CB(1) receptor immunoreactivity was significantly lower in glioblastoma multiforme (-43%, n=10; p<0.05) than in normal post-mortem brain tissue (n=16). No significant differences were found for astrocytoma (n=6) and meningioma (n=8) samples. Conversely, CB(2) receptor immunoreactivity was significantly greater in membranes of glioblastoma multiforme (765%, n=9; p<0.05) and astrocytoma (471%, n=4; p<0.05) than in control brain tissue (n=10). Finally, the maximal stimulation of [(35)S]GTPgammaS binding by WIN 55,212-2 was significantly lower in glioblastomas (134+/-4%) than in control membranes (183+/-2%; p<0.05). The basal [(35)S]GTPgammaS binding and the EC(50) values were not significantly different between both groups. The present results demonstrate opposite changes in CB(1) and CB(2) receptor protein expression in human gliomas. These changes may be of interest for further research about the therapeutic effects of cannabinoids in glial tumors.